The Objective Equivalent in Ahmad Matar's Poetry (Journal of the College of Basic Education, 2022)
The concept of our study can be summed up in clarifying the term (objective equivalent) which the poet Ahmed Matar adopted in his poetry to reach the meanings he wanted to create to be a corresponding image through his tools that benefited him in creating the image. The meaning provided by the objective equivalent, and it is created by balancing corresponding to the real images to be described, and the objective equivalent included in (Qur’anic quotation, equilibrium, poetic image, simile, comparison.